2016
DOI: 10.1590/2359-3997000000195
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of clinically relevant pituitary adenomas: retrospective cohort study in a Health Management Organization in Buenos Aires, Argentina

Abstract: Objectives:The main purpose of this study was to estimate the incidence rate and prevalence of clinically relevant pituitary adenomas (PAs) within the Hospital Italiano Medical Care Program (HIMCP), a well-defined population of 150,000 members living in the urban and suburban area of the city of Buenos Aires. We defined clinically relevant PAs as those associated with endocrine dysfunction and/or mass effect. Subjects and methods: A retrospective open cohort study was conducted, including all members of the HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 21 publications
0
53
1
6
Order By: Relevance
“…In contrast, the pituitary adenoma prevalence in Iceland evaluated in 2012 was higher (1/865) with 40% being prolactinomas, suggesting a higher prevalence of pituitary adenomas [12]. Some studies have reported incidence rates for pituitary adenomas [6,10,12,13]. Most report an increase in the incidence over the years, possibly indicating the contribution of improved access to diagnostic tools (such as MRI or hormonal assays) and improved disease recognition.…”
Section: Epidemiologymentioning
confidence: 99%
“…In contrast, the pituitary adenoma prevalence in Iceland evaluated in 2012 was higher (1/865) with 40% being prolactinomas, suggesting a higher prevalence of pituitary adenomas [12]. Some studies have reported incidence rates for pituitary adenomas [6,10,12,13]. Most report an increase in the incidence over the years, possibly indicating the contribution of improved access to diagnostic tools (such as MRI or hormonal assays) and improved disease recognition.…”
Section: Epidemiologymentioning
confidence: 99%
“…7 Similarly, the prevalence of PAs (23.1 per 100 000) was remarkably lower compared to other reports from across the globe (Figure 1). 2,3,[5][6][7]16 The reasons for the lower than expected prevalence rates for all types of SMs in our study are not entirely Figure 1. Prevalence of sellar masses in the present study compared to prevalence in other studies in other countries.…”
Section: Discussionmentioning
confidence: 88%
“…Non-functioning pituitary adenomas (NFPAs) are benign pituitary neoplasms. They account for 14-54% of pituitary adenomas which are the second most common primary brain tumors [1][2][3][4][5]. The delay in the diagnosis of NFPAs is related to the clinical manifestations of the lack of excessive hormone secretion.…”
Section: Introductionmentioning
confidence: 99%